Strategi Kursus Bahasa Inggris ELLA di Pare Kediri dalam Membentuk Nilai-Nilai Moderasi Agama - Ahsan, Nashrulloh; Susilo, Suko; Khoiruddin, Arif (Universitas Islam Negeri Sunan Ampel, 2026)
Religious moderation is a religious attitude that is balanced, tolerant, and avoids extremism, which is very relevant in the context of social and cultural diversity in Indonesia. Religious moderation does not mean equalizing all religions, but accepting and appreciating differences, and avoiding excessive attitudes (ghuluw) in religious beliefs and practices. The purpose of this research is to examine Ella English Course Pare Kediri's strategy in shaping the value of religious moderation. The research method used to explore in depth about social interactions between students who come from diverse religious, cultural, and regional backgrounds is using descriptive qualitative with data collection conducted through observation, interviews, and documentation. The results showed that the practice of religious moderation at Ella English Course Pare Kediri is reflected in social solidarity, tolerance, and harmonious interactions between students. These values are built through institutional culture, inclusive learning approaches, and the active role of teachers in shaping an open and peaceful learning environment. This research contributes to the strengthening of character education and the importance of non-formal institutions as agents of forming social harmony within the framework of religious moderation.